(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Hypothyroidism is a common endocrine disease characterized by a deficiency of thyroid hormones and has a significant impact on all body systems, especially the cardiovascular system. This scientific and literary article extensively discusses the pathophysiological effects of hypothyroidism on the cardiovascular system, the clinical effectiveness of levothyroxine-based replacement therapy, modern diagnostic approaches, and individual treatment strategies. Changes in cardiac output, peripheral vascular resistance, lipid metabolism, and endothelial function in overt and subclinical hypothyroidism are analyzed. Also, modern scientific data on the effect of levothyroxine therapy on heart failure, arterial hypertension, atherosclerosis, and arrhythmias are presented.